Генеза педагогічної підготовки вчителів США для інклюзивної школи - Бондар, Тамара; Bondar, T. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано й узагальнено ґенезу професійно-педагогічної підготовки учителів для забезпечення диверсифікованих потреб учнів загальноосвітньої (інклюзивної) школи в США на тлі законодавчих актів стосовно освіти осіб з інвалідністю. Доведено, що система педагогічної освіти для інклюзивної школи перебуває в процесі реформування.In this article the author presents the historic overview of teacher training programs created to prepare special and general educators to serve students with disabilities in the regular classroom. It is evident that teacher training programs were initiated and financed by the federal legislature. The 1967 Education Professions Development Act allocated funding for training general educators to serve in the inclusive classroom. The Education for All the Handicapped Children Act has been crucial for the development of inclusive education, expanded the powers of the previous acts, and continues to finance teachers training programs. The current teacher education reform started in 1980 because of the inclusion practices expansion. The reform is evidenced many federal initiatives, including the report of the National Commission on Excellence in Education “Nation at Risk”, The Holmes’ Group report “Tomorrow's Teachers”, National report “Redesigning teacher education teacher education”, Report of the National Commission “What Matters Most: teaching for America's future, re-authorization of the Individuals with Disabilities Education Act in 1997, No child Left Behind, Race to the Top. The reform still continues today to ensure teachers’ high qualification to meet students’ diverse needs in the regular classroom.
Training Teachers for the Inclusive Classroom in the USA: Historic Development
Keywords: інклюзивна освіта; inclusive education; педагогічна освіта; учні, які мають інвалідність; закони; диверсифіковані навчальні потреби; teacher education; students with disabilities; laws; diversified educational needs